A new Zoropsis species from China, with notes on Zoropsis pekingensis Schenkel, 1953 (Araneae, Zoropsidae) - Li, Zhiyue; Hu, Lanlan; Zhang, Feng (Zootaxa, 2015)
The family Zoropsidae is currently represented by 15 genera and 87 species (World Spider Catalog 2015). Zoropsids are medium to large size spiders, with a narrow, bipartite cribellum and calamistrum; eight eyes in two rows, anterior eye row nearly straight, posterior row strongly recurved; median furrow longitudinal; toothed chelicerae; tibiae and metatarsi I, II equipped with several pairs of ventral spines; metatarsi and tarsi bearing scopulae; two tarsal claws (Bosselaers 2002). They are often collected from houses, under stones or in leaf litter in forest.